Age-dependent effects of the β3 adrenoceptor agonist CL316,243 on human and rat detrusor muscle strips - Petereit, Charlotte; Porath, Katrin; Rackow, Simone; Kernig, Karoline; Hakenberg, Oliver W.; Köhling, Rüdiger; Kirschstein, Timo (Pflügers Archiv, 2024)
Motility of detrusor smooth muscle includes adrenergic relaxation and cholinergic contraction. Since the latter may be deregulated in overactive bladder (OAB) pathophysiology, anticholinergics are the standard therapy but occasionally less tolerated due to side effects such as dry mouth and constipation. β 3 adrenoceptor agonists also alleviate OAB symptoms by relaxing the detrusor muscle. Their age dependence, however, is far from understood. To address this issue, we induced contractions with KCl (60 mM) and carbachol (from 10 nM to 100 μM) in the presence of the β 3 adrenoceptor agonist CL316,243 (from 0.1 to 10 μM) in both human and rat muscle strips. Our results confirmed that both contractions were attenuated by β 3 adrenoceptor activation in both species, but with differing age dependence. In humans, specimens from mid-life subjects showed a significantly more pronounced effect of CL316,243 in attenuating carbachol-induced contractions than those from aged subjects (Cohen’s d of maximal attenuation: 1.82 in mid-life versus 0.13 in aged) without altering EC 50 . Conversely, attenuation of KCl responses by CL316,243 increased during ageing (Spearman correlation coefficient = -0.584, P <0.01). In rats, both KCl- and carbachol-induced contractions were significantly more attenuated by CL316,243 in samples from adolescent as compared to aged samples. Immunohistochemistry in human detrusor sections proved β 3 adrenoreceptor abundance to remain unaltered during ageing. In conclusion, our findings suggest differential age-dependent changes in human β 3 adrenoceptor-dependent attenuation of detrusor contraction in terms of electromechanical versus pharmacomechanical coupling; they may help understand the differential responsiveness of OAB patients to β 3 agents.